2011
DOI: 10.1007/s00253-011-3115-8
|View full text |Cite
|
Sign up to set email alerts
|

Direct ethanol production from cassava pulp using a surface-engineered yeast strain co-displaying two amylases, two cellulases, and β-glucosidase

Abstract: In order to develop a method for producing fuel ethanol from cassava pulp using cell surface engineering (arming) technology, an arming yeast co-displaying α-amylase (α-AM), glucoamylase, endoglucanase, cellobiohydrase, and β-glucosidase on the surface of the yeast cells was constructed. The novel yeast strain, possessing the activities of all enzymes, was able to produce ethanol directly from soluble starch, barley β-glucan, and acid-treated Avicel. Cassava is a major crop in Southeast Asia and used mainly fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…The reaction was then performed at 45 °C for 10 min and stopped by adding 150 µL of 1 mol L ‐1 Na 2 CO 3 . After 2 min centrifugation, the amount of p ‐nitrophenol released was measured at 400 nm …”
Section: Methodsmentioning
confidence: 99%
“…The reaction was then performed at 45 °C for 10 min and stopped by adding 150 µL of 1 mol L ‐1 Na 2 CO 3 . After 2 min centrifugation, the amount of p ‐nitrophenol released was measured at 400 nm …”
Section: Methodsmentioning
confidence: 99%
“…In this respect, heterologous β-glucosidases genes with different origin have been successfully cloned and expressed in S. cerevisiae strains, including those from Saccharomycopsis fibuligera [146,147], Issatchenkia orientalis [148]. Furthermore, to reduce the cellulosic ethanol production cost, a promising strategy termed as "consolidated bioprocessing" has been proposed, which involves production of all the cellulolytic enzymes (EG, CBH, BG) and fermentation of resulting sugars to ethanol [149][150][151]. Considerable success has been achieved enabling growth of recombinant S. cerevisiae on pure cellulose [152,153].…”
Section: Strain Improvementmentioning
confidence: 99%
“…Aspergillus aculeatus β-glucosidase I has been reported that it can hydrolyze soluble and insoluble cello-oligosaccharides. Apiwatanapiwat et al [8] modified a yeast strain coexpressing α-amylase, glucoamylase, endoglucanase, cellobiohydrase, and β-glucosidase that could directly produce ethanol from cassava pulp without addition of any hydrolytic enzymes during fermentation. Ito et al [9] constructed a yeast strain for APG synthesis from genetically inducing the display of β-glucosidase I from A. aculeatus No.…”
Section: Introductionmentioning
confidence: 99%